The Guidelines for Development of Academic Administration under the Spread of the Corona Virus Infection the Spread of the Corona virus infection 2019 (COVID-19) of Small Schools under Office of Kalasin Primary Educational Service Area 2 - Palapol, Taweerat; Phoojomjit, Pongphop (Journal for Developing the Social and Community, 2023)
The purposes of this research were to study the current and the desirable state and guidelines for development of academic administration under the spread of the corona virus infection the spread of the corona virus infection 2019 (COVID-19) of small schools under office of Kalasin primary educational service area 2. The research process was divided to 2 phases: Phase 1 ; to study the current and the desirable state and guidelines for development of academic administration under the spread of the corona virus infection the spread of the corona virus infection 2019 (COVID-19) of small schools. The sample group used in the research 278 people was 45 administrators, 233 teachers. The research tool was a questionnaire, confidence of the whole .79. Phase 2; to study the guidelines for development of academic administration under the spread of the corona virus infection the spread of the corona virus infection 2019 (COVID-19) of small schools. The target groups include 2 school for visiting best practices and 7 experts for assess suitability Possibility of guideline. The research results were found that : 1. The current state in overall was high average and the desirable state in overall was in the highest level. The priority need rank from high to low level was 1) Learning management in new normal (PNI Modified = .17) 2) Teacher development in new normal (PNI Modified = .16) 3) Assessment in new normal (PNI Modified = .09) 4) Participation in academic administration (PNI Modified = .08) 2. guideline for development was processes and methodologies for development academic administration under the spread of the corona virus infection the spread of the corona virus infection 2019 (COVID-19) of small schools, The guideline Include 1) principle and reason 2) objective 3) content 4) development process and 5) measurement and evaluation, feasibility and utility was the highest in overall.